2010
DOI: 10.1631/jzus.b1000125
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer cell growth inhibition by linoleic acid is related to fatty acid composition changes

Abstract: Polyunsaturated fatty acids (PUFAs) possess anti-cancer action both in vitro and in vivo. In the present study, we detected cell viability with methyl thiazolyl tetrazolium (MTT) assay and cell membrane permeability with propidium iodide (PI) fluorescence dyeing, and calculated cell membrane fluidity change as fluorescence anisotropy. Fatty acid content in cells was measured by gas chromatography/mass spectroscopy (GC/MS), and the relationship between fatty acid composition and cell viability was studied. We o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 24 publications
(30 reference statements)
2
25
0
Order By: Relevance
“…1, oleate showed no such effect compared to BSA up to 600 μM. Similar to previous reports [45,46], high concentrations (≥200 μM) of DHA or linoleate alone decreased cell viability somewhat (Fig. 9A).…”
Section: Oleate Increases Tg While Blocking Palmitate-induced Dagsupporting
confidence: 89%
“…1, oleate showed no such effect compared to BSA up to 600 μM. Similar to previous reports [45,46], high concentrations (≥200 μM) of DHA or linoleate alone decreased cell viability somewhat (Fig. 9A).…”
Section: Oleate Increases Tg While Blocking Palmitate-induced Dagsupporting
confidence: 89%
“…This is a known compound closely related to EPA (one less double bond at position 5) with an accurate mass of 304.2402. ETA is an ω-3 fatty acid naturally present in fish oils at levels of around 1-2% 27 28 whose anticancer activity has been studied 29,30 . However, previous studies did not conclude whether or not linoleic acid is active against the cancer cells tested (including colorectal, breast and lung cancer cell lines).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that in both whole organisms, as well as in cell cultures, saturated and unsaturated fats have the ability to impact a number of tissue and cellular metabolic functions [2][3][4][5][6]. The suggested mechanisms, by which these processes may be occurring, are thought to involve changes in cell membrane fluidity, and cell membrane receptor availability [7][8][9][10], as well as suppression, or up-regulation of cell-to-cell growth factor signaling [1,11,12], and inflammatory factor generation [13,14]. Saturated vs. unsaturated lipid mediated cellular behavioral changes have been shown to impact the overall behavior [15] and the fluidity of peripheral muscle tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Saturated vs. unsaturated lipid mediated cellular behavioral changes have been shown to impact the overall behavior [15] and the fluidity of peripheral muscle tissue. A direct relationship exists between an increase in polyunsaturated fatty acids and membrane fluidity, and the opposite (rigidity) in the presence of some monosaturated and predominantly saturated fatty acids, and cholesterol [10]. Membrane fluidity is believed to influence the capability of some cancer cells to metastasize [16].…”
Section: Introductionmentioning
confidence: 99%